Géométrie, Topologie, Riemann, et les nuances vivantes de la pensée mathématique chez Bachelard (avec un contrepoint autour de Simone Weil) - Zalamea, Fernando (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
In this paper we examine many Bachelard references to geometry and topology, and, in particular, to Riemann’s work. Building on those readings, we propose a “living geometry” perspective on Bachelard’s understanding of mathematics, according to some contemporary geometry trends. In counterpoint with Bachelard, we provide a footnote apparatus (basso continuo), around Simone Weil’s reflections on mathematical thought.